2014 IFPRI Annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
Nutrients are a building block of life. Yet millions of people suffer from undernutrition and micronutrient malnutrition globally. The scope of impact is staggering: a lack of nourishment can lead to a lifetime of challenges, including stunted cognitive development, which can be passed on to future generations. Beyond its human toll, undernutrition costs the global economy 2 to 3 percent of Gross Domestic Product (GDP) every year, according to the FAO. It is because of nutrition’s ubiquitous role in well-being that IFPRI and partners brought the issue to center stage in 2014, launching the first annual Global Nutrition Report (GNR). The GNR tracks worldwide progress in improving nutrition, identifies bottlenecks to change, highlights opportunities for action, and contributes to strengthened nutrition accountability.